Evidential approaches to the knowledge investigation in the higher medical education - S. I. Karas (Бюллетень сибирской медицины, 2004)
In the article the point of view of medical knowledge as an object of investigation with certain properties has been presented. Evidential approaches to such investigation included analysis and synthesis of knowledge and were supported by the developed computer programs. The higher medical education has been viewed as the dynamics of students’ knowledge model.